Genetic characteristics and phylogeography of the habitat generalist mayfly Ecdyonurus yoshidae (Ephemeroptera: Heptageniidae) in the Japanese archipelago - Kaneko, Hiroaki; Ishiwata, Shin‐ichi; Bae, Yeon Jae; Takamura‐Enya, Takeji (Entomological research, 2021)
Because of their early divergence in insect evolution, unique aquatic larval stage, and low dispersal ability, many mayfly species exhibit genetic structures that accurately reflect geological history and paleoclimatic changes. The present study investigated the genetic characteristics of Ecdyonurus yoshidae Takahashi (Ephemeroptera: Heptageniidae), a mayfly that inhabits a variety of freshwater habitats in Japan. Mitochondrial cytochrome c oxidase subunit I ( COI ) and 16S ribosomal RNA ( 16S rRNA ) gene sequences were generated from 209 mayfly specimens that were collected from 109 sites in Japan. A total of 145 haplotypes were detected, and nine of the lineages exhibited geographical regionality, with one lineage being endemic to Lake Biwa. The haplotype network was “bottleneck type” and included both star‐like structures and missing (or unobserved) haplotypes. Together, the haplotype network and F ST values indicated that the Fukuejima Island group (Clade I) was genetically distinct from groups on the island of Kyushu, which is separated from Fukuejima Island by the Gotonada Sea. The common ancestor of E. yoshidae lineages in Japan was estimated to have diverged 1.14 mega‐annum (Ma) (95% highest posterior density interval, 0.55–1.78 Ma), and more regional genetic diversities were generated during the Middle to Late Pleistocene. Genetically distinct lineages of eastern and western Japan were separated by the Kinki Triangle region in central Japan. The genetic diversity of the habitat generalist E. yoshidae increased during the Middle and Late Pleistocene, when crustal movement and climate change in the Japanese archipelago occurred simultaneously.